Pelatihan Visual Branding dan Narasi Visual Sebagai Sarana Pemasaran Digital Produk Tata Boga di SMK N 1 Ampek Angkek - Cindi Adelia Putri Emas; Ermi Rosmita (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
Students of the Culinary Arts Department at SMK N 1 Ampek Angkek face challenges due to their limited ability to build branding for the products they have created. Most of them are only capable of producing food products, but they have not yet developed the skills to promote those products effectively. This training activity aims to enhance students’ skills in product photography and storytelling so that they can create and build branding for their products. The methods used in this activity include several stages: the initial survey and observation stage, the implementation stage, the evaluation stage, and the follow-up stage. The training was conducted in two main formats: (1) delivering materials through lectures and QA sessions, and (2) hands-on practice in photographing and writing narratives based on the photos they had previously taken. The training was attended by twenty-five Culinary Arts students selected from various classes and grade levels. The results of this activity showed a significant improvement in the skills of Culinary Arts students at SMK N 1 Ampek Angkek in building visual branding and composing narratives useful for promoting their products. Moreover, this community service activity also fostered students’ motivation to market their products to a broader audience. From this activity, it can be concluded that 92% of the students reported experiencing significant improvement in their photography and narrative-building skills to support their product branding efforts.